The Delays For Signalized Intersection Using Atcs DataAnd Field Survey Method (Case Study At Simpang Tiga Kerten, Surakarta) - Magfirona, Alfia; , Nurul Hidayati, ST., MT., Ph.D (2014)
The increasing of traffic volume in Surakarta has caused an increasing of congestion in several road networks. One of traffic jam phenomenon at intersection especially in peak hour can be found at some signalized intersections and roads especially in Simpang Tiga Kerten. It is located at the meeting between Jl. Slamet Riyadi and Jl. Ahmad Yani, Surakarta. The Local Government through the Communication, Informatics and Transportation Department (Dishubkominfo) Surakarta is developing integrated traffic management control system named Area Traffic Control System (ATCS). The aim of ATCS is to enable the vehicle movement continuously and minimize the delay in intersection (Risdiyanto, 2014). Traffic delay at signalized intersection is used as an indicator to evaluate the performance of intersection refers to MKJI 1997. The using of MKJI 1997 method for the traffic condition at present needs to be evaluated. The delay value needs to be compared with the result of field survey method using ATCS. The implementation of manual traffic counts survey carried out for a day mainly at morning peak hour (06:00-07:00 AM). It is sourced from traffic counting data from ATCS detector of Dishubkominfo Surakarta after converted in passanger cars unit. The obtained data from field observation for calculating field delay are number of waiting vehicle every15 seconds, stopped (in red and amber time) and not stopped vehicles (in green and amber time). The average delay values by MKJI 1997 method at Simpang Tiga Kerten, Surakarta is 105.50 sec/pcu, while the average field delay values is 16.19 sec/pcu. Based on the comparison, it can be known that the field delay is lower than MKJI 1997 delay. It is caused by the differences in withdrawal traffic flow data that will be used in delay calculation analysis. Inaccurate of determining the adjustment values (which are: effective width, city size, side friction, turning movement, vehicles stopped ratio and turn at each approach will also cause inaccurate in the delay value.